Workers' competency, performance and competitiveness in Malaysia's Private education sector - Ishak Yussof; Rahmah Ismail; Zulkifly Osman (Penerbit Universiti Kebangsaan Malaysia, 2011)
In Malaysia, the education sector, in particular the private education sector has been expanding rapidly as a result of government policy in liberalizing the sector and to turn Malaysia as a centre of excellence in the educational provision within the Asian region. This subsequently requires amore competent and competitiveworkforce to spearhead the expension of this sector. This article aims to investigate determinants of workers competency performance and competitive workplace . The analysis in this article is based on 567 executives/profesionals in the private education sector in four major states, namely Selangor, Penang, Federal Territory and Johor. The Study will compute the worker competency and performance indices on several determinant factors, which include human capital, employee attributes and personal characteristerics variables. The linear regresion model and ordinary least squared (OLS)procedure will be used in the data analysis. Our analysis shows that most of the human capital variables and workers attributes contributed significantly to workers competency and subsequently their competitiveness.